2018
DOI: 10.1097/bot.0000000000001255
|View full text |Cite
|
Sign up to set email alerts
|

Pedicled Vascularized Bone Graft of the Distal Radius for Recalcitrant Nonunion of the Distal Humerus

Abstract: Objectives: To analyze the clinical and radiological outcomes of a series of patients treated with a pedicled vascularized bone graft (VBG) of the distal radius for the treatment of recalcitrant atrophic nonunions of the distal humerus. Design: Retrospective clinical study. Setting: University-affiliated teaching hospital. Patients: Fifteen patients with supracon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
6
0
3
Order By: Relevance
“…Osseous healing was defined as the presence of at least three of four healed cortices on plain radiography, and CT was not routinely performed unless it was difficult to judge healing on plain radiography [ 4 ]. The Mayo Elbow Performance Index (MEPI) was calculated preoperatively and at the most recent follow-up visit for each patient [ 17 ]. A MEPI score of 90–100 was considered an excellent result, 75–89 was considered good, 60–74 was considered fair, and less than 60 was considered poor.…”
Section: Methodsmentioning
confidence: 99%
“…Osseous healing was defined as the presence of at least three of four healed cortices on plain radiography, and CT was not routinely performed unless it was difficult to judge healing on plain radiography [ 4 ]. The Mayo Elbow Performance Index (MEPI) was calculated preoperatively and at the most recent follow-up visit for each patient [ 17 ]. A MEPI score of 90–100 was considered an excellent result, 75–89 was considered good, 60–74 was considered fair, and less than 60 was considered poor.…”
Section: Methodsmentioning
confidence: 99%
“…Although distal humerus fractures account for a small percentage of all fractures [ 1 ], high complication rates have been reported after surgical treatment due to fracture complexity and poor bone quality [ 2 , 3 ]. It is reported that up to 25% of non-unions occur after distal humerus fracture surgery [ 4 , 5 ]; in most cases, further operative treatment with revision ORIF or total elbow arthroplasty is necessary [ 5 , 6 ]. Vauclair et al reported that when additional surgery is performed for non-union, a very high complication rate and unsatisfactory results may still occur [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that a mix of 2/3 auto-and 1/3 allografts as reported by Karger et al [12] could also lead to bone healing, but this was not experimented in our cases. Vascularized bone or vascularized periosteal grafts, either pedicled as reported by Zaidenberg et al from the distal radius [17] or by microsurgical technique [18] are other options, possibly indicated in the case of poor soft tissue bed and large bone defect, but seem to be technically more challenging. Whatever type of bone grafting, we recommend a two-stage procedure according to Maquelet in the case of an active or suspected infection, which was the case only in one patient of this small series.…”
Section: Discussionmentioning
confidence: 99%